Aspects of management that influence the process of municipal and regional planning of the Unified Health System - Vicentine, Fernanda Bergamini; Delatorre, Thatiane; Feltrin, Aline Fiori dos Santos; Nakata, Liliane Cristina; Soares, Letícia; Ferreira, Janise Braga Barros (Medicina (Ribeirao Preto), 2018)
Study model: Descriptive, cross-sectional study with a qualitative approach. Objectives of the study: to describe and analyze the opinion of managers and technicians of the health sector on the instruments and resources that integrate the planning process in Unified Health System. Methodology: 26 participants were interviewed, among managers and technicians from the municipalities and the state that make up the Regional Health Department XIII. To analyze the data, we used Content Analysis in its thematic aspect. Results: The regional planning and co-management space, known as the Regional Management Collegiate, proven to be influential for the exchange of experiences, but it showed weaknesses about the lack of cohesion due to the different levels of managerial knowledge and diverse financial conditions among the municipalities. It was noticed that the permanence of the managers in the positions was positive, as long as accompanied by practices of permanent education. Finally, the construction and execution of the planning had as main barriers the underfinancing and the judicialization in health, leading some municipalities to choose policies to induce the federal level and outsourcing the hiring of human resources. Conclusion: The Collegiate of Regional Managers presented great potential and could collaborate with the reduction of setbacks, with each political discontinuity, in the process of municipal and regional planning if the greater focus given to federative coordination and state technical contribution.